Interactions between the otitis media gene, Fbxo11, and p53 in the mouse embryonic lung - Tateossian,H; Morse,S; Simon,MM; Dean,CH; Brown,SDM (Disease Models & Mechanisms, 2015)
Otitis media with effusion (OME) is the most common cause of hearing loss in children, and tympanostomy (ear tube insertion) to alleviate the condition remains the commonest surgical intervention in children in the developed world. Chronic and recurrent forms of otitis media (OM) are known to have a very substantial genetic component; however, until recently, little was known of the underlying genes involved. The Jeff mouse mutant carries a mutation in the Fbxo11 gene, a member of the F-box family, and develops deafness due to a chronic proliferative OM. We previously reported that Fbxo11 is involved in the regulation of transforming growth factor beta (TGF-β) signalling by regulating the levels of phospho-Smad2 in the epithelial cells of palatal shelves, eyelids and airways of the lungs. It has been proposed that FBXO11 regulates the cell's response to TGF-β through the ubiquitination of CDT2. Additional substrates for FBXO11 have been identified, including p53. Here, we have studied both the genetic and biochemical interactions between FBXO11 and p53 in order to better understand the function of FBXO11 in epithelial development and its potential role in OM. In mice, we show that p53 (also known as Tp53) homozygous mutants and double heterozygous mutants (Jf/+ p53/+) exhibit similar epithelial developmental defects to Fbxo11 homozygotes. FBXO11 and p53 interact in the embryonic lung, and mutation in Fbxo11 prevents the interaction with p53. Both p53 and double mutants show raised levels of pSMAD2, recapitulating that seen in Fbxo11 homozygotes. Overall, our results support the conclusion that FBXO11 regulates the TGF-β pathway in the embryonic lung via cross-talk with p53.